Pathogenic relationship between phenotypes of ARPKD and novel compound heterozygous mutations of PKHD1 - Zhang, Xinrong; Wu, Jiebin; Zhou, Jianteng; Liang, Jie; Han, Yu; Qi, Yunmeng; Zhu, Tao; Yuan, Dejian; Zhu, Zuobin; Zhai, Jingfang (Frontiers in Genetics, 2024)
Background: To investigate whether the novel mutation of PKHD1 could cause polycystic kidney disease by affecting splicing with a recessive inheritance pattern.A nonconsanguineous Chinese couple with two recurrent pregnancies showed fetal enlarged echogenic polycystic kidney and oligoamnios were recruited. Pedigree WES, minigene splicing assay experiment and following bioinformatics analysis were performed to verify the effects, and inheritance pattern of diseasing-causing mutations.Results: WES revealed that both fetuses were identified as carrying the same novel mutation c.3592_3628+45del, p.? and c.11207 T>C, p.(Ile3736Thr) in the PKHD1 gene (NM_138694.4), which inherited from the father and mother respectively. Both bioinformatic method prediction and minigene splicing assay experience results supported the mutation c.3592_3628+45del, p.? affects the splicing of the PKHD1 transcript, resulting in exon 31 skipping. Another missense mutation c.11207 T>C, p.(Ile3736Thr) has a low frequency in populations and is predicted to be deleterious by bioinformatic methods.These findings provide a direct clinical and functional evidence that the truncating mutations of the PKHD1 gene could lead to more severe phenotypes, and cause ARPKD as a homozygous or compound heterozygous pattern. Our study broadens the variant spectrum of the PKHD1 gene and provides a basis for genetic counseling and diagnosis of ARPKD.